2018
DOI: 10.1111/sltb.12490
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Feasibility and Effectiveness of an Australian Safety Planning Smartphone Application: A Pilot Study Within a Tertiary Mental Health Service

Abstract: The BeyondNow safety planning smartphone application was shown to be feasible and effective as an adjunct to mental health treatment among patients at risk of suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
130
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(133 citation statements)
references
References 23 publications
1
130
0
2
Order By: Relevance
“…Six of the identified studies were conducted in Australia (33%) [35,38,41,42,44,49], four in the USA (22%) [36,37,39,45], and eight in Europe (44%) [40, 43, [36, 38-40, 50, 52], and two on self-monitoring using Ecological Momentary Assessment [46,52]. One intervention focussed on Dialectical Behaviour Therapy (DBT) [45], one on Acceptance and Commitment Therapy (ACT) [42], and one was a brief contact intervention involving text messages providing links to a range of therapeutic strategies [49].…”
Section: Phasementioning
confidence: 99%
See 3 more Smart Citations
“…Six of the identified studies were conducted in Australia (33%) [35,38,41,42,44,49], four in the USA (22%) [36,37,39,45], and eight in Europe (44%) [40, 43, [36, 38-40, 50, 52], and two on self-monitoring using Ecological Momentary Assessment [46,52]. One intervention focussed on Dialectical Behaviour Therapy (DBT) [45], one on Acceptance and Commitment Therapy (ACT) [42], and one was a brief contact intervention involving text messages providing links to a range of therapeutic strategies [49].…”
Section: Phasementioning
confidence: 99%
“…No other high-risk groups (e.g., older adults, gender and sexual minorities) were specifically targeted in the identified studies. Five (28%) and two (11%) studies required participants to be clients of a mental health service [36,38,39,50,52] or school counsellor [35,41] respectively, through whom the intervention was administered. Only three studies (17%) had exclusion criteria related to high suicide risk [42][43][44].…”
Section: Phasementioning
confidence: 99%
See 2 more Smart Citations
“…Despite this scientific evidence, a literature review [ 29 ] identified very few suicide-specific apps (n=24) that include safety planning (n=14) and that directly allow the user to seek support (n=13). Feasibility studies of these apps report a significant reduction of suicidal ideation in patients and a significative augmentation of suicide-related coping [ 30 ]. However, potentially harmful content might encourage self-harm and suicide [ 31 ], and many of the existing apps for suicide prevention have not been scientifically validated [ 22 , 29 ].…”
Section: Introductionmentioning
confidence: 99%